Some saturation classes for deferred Riesz and deferred Nörlund means - SEZGEK, Şeyda; DAĞADUR, İlhan and ÇATAL, Cumali (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
One of main problem in approximation theory is determining a saturation class for a given method. The problem of determining a saturation class has been considered by Zamanski, Sunouchi, Watari and others. Mohaparta and Russel have considered some direct and inverse theorems in approximation of functions. Sunouchi and Watari have studied the Riesz means of type n. In [5], Goel et al. have extended these results by considering Nörlund means. In this paper, we examine some direct and inverse theorems in approximation of functions under weaker conditions by considering Deferred Riesz means and Deferred Nörlund means. Also, we extent above mentioned results. Mathematics Subject Classification (2010): 41A40, 41A25, 40C05, 42A05, 40D25. Received 28 March 2024; Accepted 24 May 2024.